Relationship of Cardiovascular System Health with The Event of Dementia at The Age of 50-60 Years at Haji Hospital - ansari, zaim (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
Dementia is a syndrome in which there is a deterioration in memory, thinking, behavior, and the ability to perform daily activities. Several studies have shown an association between the development of cognitive impairment and dementia with educational attainment, and lifestyle-related risk factors, such as physical activity, tobacco use, unhealthy diet, and harmful alcohol use. Dementia can be identified using the MMSE ( Mini-Mental State Examination ). Furthermore, certain medical conditions are associated with an increased risk of developing dementia, including hypertension, diabetes, dyslipidemia, obesity, and depression. The ideal cardiovascular health score also referred to as Life’s Simple 7, consists of four indicators of health behavior, and three biologics. analysis using a cross-sectional design, which was carried out at the Haji Hospital, from December 2020 – March 2021 and involved 70 respondents. Data were obtained through medical records and interviews. Based on the results of the study, the results of Somer’s d correlation test obtained p value = 0.000 (p <0.05) so that there was a significant relationship between Cardiovascular System Health and Dementia Incidence at the Age of 50-60 Years. There is a Relationship between Cardiovascular System Health and Dementia Incidence at the Age of 50-60 Years.